DIFFERENCE OF THE INDIVIDUAL YARNS IN THE COMPOSITION OF A WRAPPED YAR ON THE QUALITY OF THE YAR AND DETERMINATION OF ACCEPTABLE VALUES OF THE MAIN FACTORS AFFECTING THEIR PRODUCTION - Atambayev, Dinmuhammad (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this paper, the influence of the difference in the length of individual threads on the quality of the thread during the winding process was determined. These values ​​​​were plotted on a graph and analyzed for the influence of the machine on the stiffness of the yarn. The boundary parameters of the main factors affecting the operation of the improved working part of the yarn-winding machine were determined, and their optimal values ​​were determined using the mathematical planning method. Graphs were constructed and analyzed on the effect of these values ​​on the yarn tightness during machine operation.